Influence of harvest season and maturation stage on fragant granadille and acid passion fruit in cerrado conditions - Veras, Murilo Carlos Muniz; Pinto, Alberto Carlos de Queiroz; Menezes, Josivan Barbosa de (Pesquisa Agropecuaria Brasileira, 2000)
This work has the objective to evaluate fruit of fragrant granadille (Passiflora alata Dryand.) and acid passion fruit (Passiflora edulis Sims f. flavicarpa Deg.) in climatic conditions of Brasília, DF, Brazil, according to the harvest season and maturation stage. A completely randomized design with treatments in a 2x2x2 factorial scheme referring to species, season and maturation stage, with five replications and three samples in each replication was used. Physical-chemical evaluations were conducted on soluble solids contents, total titrable acidity, total sugars, reducing sugars, non-reducer sugars. The acid passion fruit showed desirable atributes of market quality to be consumed as fresh fruit and for processing, in both harvest seasons and maturation stages tested. Fragrant granadille presented more sugars at cold season. Anticipation of harvest might be done up to four days, for fragant granadille, and up to eight days before fruit falling, for the acid passion fruit, without interfering on the quality, allowing longer periods to trading, with smaller risk of losing fruit quality.